Unveiling transfusions: Analyzing blood product utilization patterns in a leading tertiary care center in Madhya Pradesh, India - Suresh Kumar Sutrakar,; Sakshi Chaurasia,; Parul Singh Rajpoot,; Shambhavi,; Priyanka Agrawal,; Lokesh Tripathi,; Uday Raj Singh,; Sadhana Yadav, (Asian Journal of Medical Sciences, 2024)
Background: Blood transfusions play a pivotal role in medical care, saving millions of lives annually. The timely provision of safe blood is critical in various clinical scenarios, necessitating a careful balance between supply and demand. Despite advanced blood banking facilities globally, challenges persist in ensuring appropriate blood component utilization, prompting a need for clinical audits and optimization strategies. Aims and Objectives: This study aims to analyze the patterns of blood product utilization in a tertiary care hospital in Madhya Pradesh over 1 year, focusing on transfusion requests, cross-match-to-transfusion (C/T) ratios, transfusion indices (TIs), and indications for transfusions. Materials and Methods: A retrospective study was conducted at Shyam Shah Medical College from January 01, 2023, to December 31, 2023. Data from transfusion and cross-match requests in various departments were collected. C/T ratios, TI, and non-usage probability were computed to assess blood utilization efficiency. Results: Out of 16,682 cross-matched units, 71.93% were transfused. The overall C/T ratio was 1.39. The department of medicine demonstrated the most efficient blood usage with a C/T ratio of 1.16. Obstetrics and gynecology had the highest TI (1.06), while surgery had the lowest (0.71). Indications for transfusion included anemia (29.9%), pre-operative (17.2%), intraoperative (21.8%), and post-operative (31.1%). Conclusion: This study provides valuable insights into blood utilization patterns, offering a foundation for refining transfusion practices and enhancing the efficiency of blood management in the studied tertiary care hospital.